Determinants of changes in FEV1 over a workshift. Issue 3 (March 1985) - Enarson, D A; Yeung, M
Abstract : Measurement of workshift change in FEV1 is a useful predictor of respiratory disease among cotton workers and grainhandlers. Certain factors affect this measurement and must be considered in the analysis. Response varies with the time of day at which the measurement is taken. Tobacco smoking, immediate skin reactivity to common allergens, age, and initial level of FEV1 are other factors that must be considered when this measurement is used to study effects of occupational exposure to respiratory hazards.